Качественный анализ одного класса популяционных моделей с комменсальным взаимодействием - Герасин, С.Н.; Яковлев, С.В.; Яловега, И.Г. (Кибернетика и системный анализ, 2012)
Проведено якісний аналіз одного класу динамічних популяційних моделей, які взаємодіють за типом коменсалізму та конкурують за спільний субстрат. Досліджено питання щодо стійкості всіх стаціонарних станів. Аналітично знайдено всі особливі точки, отримано обмеження на характеристики росту видів та вхідні потоки субстрату та продукту. Проаналізовано якісні зміни у динаміці, що обумовлена варіаціями декількох параметрів системи, побудовано біфуркаційні діаграми для всіх особливих точок. This paper performs the qualitative analysis of a class of dynamic population models of commensal interaction of species competing for one substratum. The stability of all the stationary conditions is analyzed. All the special points are pointed out analytically and constraints are obtained for species growth characteristics and initial flows of the substratum and product. The qualitative changes in the dynamics due to variations of several system parameters are analyzed and bifurcational diagrams are plotted for all of the singular points.